Exposure to multiple mycotoxins, environmental enteric dysfunction and child growth: Results from the AflaCohort Study in Banke, Nepal. Issue 2 (12th January 2022) - Andrews‐Trevino, Johanna; Webb, Patrick; Shrestha, Robin; Pokharel, Ashish; Acharya, Sudikshya; Chandyo, Ram; Davis, Dale; Baral, Kedar; Wang, Jia‐Sheng; Xue, Kathy; Ghosh, Shibani
Abstract: Evidence of the impact of exposure to multiple mycotoxins and environment enteric dysfunction (EED) on child growth is limited. Using data from a birth cohort study, the objectives of this study were to (a) quantify exposure to multiple mycotoxins (serum aflatoxin [AFB1 ] and ochratoxin A [OTA], urinary fumonisin [UFB1 ] and deoxynivalenol [DON]), as well EED (lactulose:mannitol [L:M] ratio); (b) examine the potential combined effects of multiple mycotoxin exposure and EED on growth. Multivariate regressions were used to identify associations between growth measurements (length, weight, anthropometric z ‐scores, stunting and underweight) at 24–26 months of age and exposure to mycotoxins and EED at 18–22 months ( n = 699). Prevalence of AFB1, DON, OTA and UFB1 exposure ranged from 85% to 100%; average L:M ratio was 0.29 ± 0.53. In individual mycotoxin models, AFB1 exposure was negatively associated with weight, WAZ, increased odds of stunting (odds ratio [OR]: 1.28, 95% confidence interval [CI]: 1.08, 1.52; p = 0.004) and underweight (OR: 1.18, 95% CI: 1.00, 1.38; p = 0.046). Irrespective of other mycotoxin exposure and presence of EED, AFB1 was negatively associated with length, weight, head circumference, LAZ and WAZ, and with increased odds of stunting and underweight, UFB1 was associated with increased odds of underweight, and DON was negatively associated with head circumference. EED was associated with the impaired length and weight. These findings suggest that certain mycotoxins and EED may have independent impacts on different facets of growth and that aflatoxin dominates such impacts. Thus, programs reducing exposure to mycotoxin and EED through multi‐sectoral nutrition‐sensitive interventions have the potential to improve child growth. Key messages: Mycotoxin exposure was highly prevalent in children aged 18–22 months. Various mycotoxins and EED contribute independently to different manifestations of poor child growth AFB1 was negatively associated with length, weight, head circumference, LAZ, as well as WAZ, and associated with increased odds of stunting and underweight. UFB1 was also associated with increased odds of underweight. DON was negatively associated with head circumference.